Deficiency of Mineralization-Regulating Transcription Factor Trps1 Compromises Quality of Dental Tissues and Increases Susceptibility to Dental Caries - Socorro, Mairobys; Hoskere, Priyanka; Roberts, Catherine; Lukashova, Lyudmila; Verdelis, Kostas; Beniash, Elia; Napierala, Dobrawa (Frontiers in Dental Medicine, 2022)
Dental caries is the most common chronic disease in children and adults worldwide. The complex etiology of dental caries includes environmental factors as well as host genetics, which together contribute to inter-individual variation in susceptibility. The goal of this study was to provide insights into the molecular pathology underlying increased predisposition to dental caries in trichorhinophalangeal syndrome (TRPS). This rare inherited skeletal dysplasia is caused by mutations in the TRPS1 gene coding for the TRPS1 transcription factor. Considering Trps1 expression in odontoblasts, where Trps1 supports expression of multiple mineralization-related genes, we focused on determining the consequences of odontoblast-specific Trps1 deficiency on the quality of dental tissues. We generated a conditional Trps1Col1a1 knockout mouse, in which Trps1 is deleted in differentiated odontoblasts using 2.3kbCol1a1-CreERT2 driver. Mandibular first molars of 4wk old male and female mice were analyzed by micro-computed tomography (μCT) and histology. Mechanical properties of dentin and enamel were analyzed by Vickers microhardness test. The susceptibility to acid demineralization was compared between WT and Trps1Col1a1cKO molars using an ex vivo artificial caries procedure. μCT analyses demonstrated that odontoblast-specific deletion of Trps1 results in decreased dentin volume in male and female mice, while no significant differences were detected in dentin mineral density. However, histology revealed a wider predentin layer and the presence of globular dentin, which are indicative of disturbed mineralization. The secondary effect on enamel was also detected, with both dentin and enamel of Trps1Col1a1cKO mice being more susceptible to demineralization than WT tissues. The quality of dental tissues was particularly impaired in molar pits, which are sites highly susceptible to dental caries in human teeth. Interestingly, Trps1Col1a1cKO males demonstrated a stronger phenotype than females, which calls for attention to genetically-driven sex differences in predisposition to dental caries. In conclusion, the analyses of Trps1Col1a1cKO mice suggest that compromised quality of dental tissues contributes to the high prevalence of dental caries in TRPS patients. Furthermore, our results suggest that TRPS patients will benefit particularly from improved dental caries prevention strategies tailored for individuals genetically predisposed due to developmental defects in tooth mineralization.